Consensus statement on indications for anti-angiogenic therapy in the management of corneal diseases associated with neovascularisation: outcome of an expert roundtable - Cursiefen, Claus; Colin, Joseph; Dana, Reza; Diaz-Llopis, Manuel; Faraj, Lana A.; Garcia-Delpech, Salvador; Geerling, Gerd; Price, Francis W.; Remeijer, Lies; Rouse, Barry T.; Seitz, Berthold; Udaondo, Patricia; et al. (British Journal of Ophthalmology, 2012)
The cornea is the clear window at the front of the eye and is the eye's main refractive medium. Its transparency is essential for vision. Corneal neovascularisation is a common clinical problem with serious consequences for vision; it can compromise corneal transparency and plays a major role in corneal graft rejection by breaching corneal immune privilege. In this review, we formulate a consensus on the unmet medical needs in the management of corneal neovascularisation and outline a framework for the clinical research that is needed to identify suitable agents to meet these needs.
EVALuna2:21219